Karakter Morfologi Genotipe Jarak Kepyar (Ricinus communis L.) Tahan Penyakit Layu Fusarium - Prameswari, Rosabela Sayu; Waluyo, Budi (Universitas Wiralodra, 2023)
The castor bean (Ricinus communis L.) is a plant with a lot of potential as a vegetable oil producer. Castor bean productivity in Indonesia was 1.36 thousand tons in 2013, but it fell to 1.30 thousand tons in 2014. Fusarium wilt is one of the challenges in increasing castor bean production. Resistant genotypes can be used to control Fusarium wilt in an environmentally friendly manner. The goal of this study was to determine the variability and superior performance of Fusarium wilt-resistant castor beans. The study took place at the Faculty of Agriculture's greenhouse Experimental farm, Universitas Brawijaya in Lowokwaru District, Malang, East Java, from January to July 2021. Twenty two genotypes resistant to Fusarium wilt, urea fertilizer, NPK, and pesticides were used. Augmented design was used as the experimental field design. Following Pearson correlation type and coefficient of variation, variability was investigated using principal component analysis (PCA). Based on PCA, the variability of morphological characters of 22 genotypes of castor bean is divided into first-nine principal components with a cumulative variability of 85.91 percent. The coefficient of variation for the main raceme weight character is 61.15 percent. The TBN 0816-36 genotype succeeds in vegetative characters, while the CT4-10-3-(C864-3)-68 genotype performs best in yield.